Hukum Dan Usaha Remaja Masjid Mukhtarul Arifin Perumahan Cipta Asri Kelurahan Tembesi Kota Batam - Ukas Ukas; Moh. Andika Surya Lebang; Padrisan Jamba; Risca Azmiana (LPPM Universitas Putera Batam, 2023)
The material provided in this coaching is divided into 2 groups, namely the legal group and the business group aimed at